Evaluation of E-Learning Lessons for Strengthening Early Childhood Practitioner Use of Family Capacity-Building Practices - J., Dunst, C.; B., Howse, R.; D., Embler; W., Hamby, D. (International Journal of Educational Technology and Learning, 2018)
Findings from a case study field-test evaluation of e-learning lessons for promoting early childhood intervention practitioners’ understanding and use of family capacity-building practices are described. Participants were two early childhood program directors, two early childhood technical assistance providers, and two early childhood intervention practitioners. Pattern matching was used to evaluate whether or not participants with different roles and responsibilities judged the instructional design, interactivity, video illustrations, and usefulness of the e-learning lessons similarly or differently. Results indicated that the different features of the e-learning lessons were rated highly by all but one participant and that the patterns of responses were much the same regardless of participants’ professional roles or responsibilities. Participant feedback and suggestions were used to revise the e-learning lessons and correct technical problems.